2017
DOI: 10.3389/fphar.2017.00511
|View full text |Cite
|
Sign up to set email alerts
|

Eupatorium fortunei and Its Components Increase Antiviral Immune Responses against RNA Viruses

Abstract: Eupatorium fortunei (EF) has long been used as herbal medicine in Korea, China, and Asian countries to treat a variety of diseases. Recent studies have reported that EF has anti-metastatic, anti-angiogenic, anti-bacterial, and anti-oxidant activities, as well as activities against malignant metastatic human cancers. The effect of EF and its components on viruses has not been reported. In the present study, the antiviral activity and mechanism of action of an aqueous extract of EF (WEF) and its components were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 35 publications
0
35
0
Order By: Relevance
“…The inhibition of viral replication was assayed as previously described 25 . Briefly, MDCK cells were cultured in 96-well plates (2 × 10 4 cells/well) for 16 h. Then differing GHE concentrations (100 or 200 μg/mL) were added to H1N1 [multiplicity of infection (MOI) = 1] and A/PR/8/34-GFP (MOI = 1) and the mixtures were incubated at 37 °C for 1 h. MDCK cells were infected with these mixtures at 37 °C for 2 h. Afterwards, the virus was removed, and cells were washed three times with PBS, and the medium was replaced by complete DMEM.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The inhibition of viral replication was assayed as previously described 25 . Briefly, MDCK cells were cultured in 96-well plates (2 × 10 4 cells/well) for 16 h. Then differing GHE concentrations (100 or 200 μg/mL) were added to H1N1 [multiplicity of infection (MOI) = 1] and A/PR/8/34-GFP (MOI = 1) and the mixtures were incubated at 37 °C for 1 h. MDCK cells were infected with these mixtures at 37 °C for 2 h. Afterwards, the virus was removed, and cells were washed three times with PBS, and the medium was replaced by complete DMEM.…”
Section: Methodsmentioning
confidence: 99%
“…The cells were incubated for 48 h at 37 °C with 5% CO 2 . The reduction of viral cytopathic effect was determined by measuring cell viability measured using MTS assay as described above 25 . Influenza virus GFP expression was measured under a fluorescence microscope (Olympus, Tokyo, Japan) following 24 h of viral infection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, Choi et al found that psoralen significantly inhibited the replication of A/PR/8/34 H1N1 virus and induced macrophages to secrete antiviral cytokines such as interferon-beta (IFN-β). Choi et al, 2017 . A recent study found that low concentrations of IFN-β can significantly inhibit Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infection ( Mantlo et al, 2020 ).…”
Section: Antiviral and Antibacterial Effects Of Psoralenmentioning
confidence: 99%
“…Eupatorium fortune is a herbal medicinal plant belonging to Korea, China, and Asian countries with antibacterial and antioxidant activities and anticancer activity. Recent studies have reported that eupatorium fortune can inhibit a number of RNA viruses including human coronaviruses (Choi et al 2017). As these herbal drugs demonstrated potential antiviral activity against CoVs, there is an urgent need to establish their effectiveness in humans and approve in a dose-dependent manner from various organizations like Food and Drug Administration (FDA).…”
Section: Herbal Medicines Showing Efficacy Against Coronavirus In Celmentioning
confidence: 99%